Co/Se and Ni/Se nanocomposite films prepared by magnetron sputtering as counter electrodes for dye-sensitized solar cells. (1st March 2019) - Wu, Xuedan; Duan, Jialong; Zhao, Yuanyuan; Yang, Xiya; Chen, Haiyan; He, Benlin; Tang, Qunwei
Graphical abstract: Co/Se and Ni/Se nanocomposite films deposited on FTO glasses via magnetron sputtering are used as counter electrodes in dye-sensitized solar cells, yielding a maximized power conversion efficiency of 6.43%. Highlights: Co/Se and Ni/Se nano-films are prepared by magnetron sputtering method. The as-prepared films are employed as CEs for DSSCs. The DSSC with Co/Se CE delivers a PCE of 6.43%. Abstract: Dye-sensitized solar cells are promising solutions to energy and environmental problems. By addressing the high cost of preferred platinum counter electrode, Co/Se and Ni/Se nanocomposite counter electrodes are prepared by magnetron sputtering targets onto fluorine-doped tin oxide glass for dye-sensitized solar cell applications. The binary nanocomposite counter electrodes exhibit superior electrocatalytic activity toward I3 − reduction compared to pure Ni, Se and Co electrodes. In particular, the dye-sensitized solar cell based on Co/Se counter electrode achieves a power conversion efficiency of 6.43%, which is much higher than 0.87%, 2.91%, 3.77% and 5.23% for Ni, Se, Co and Ni/Se solar cells, respectively. The preliminary results demonstrate it is a promising strategy to prepare robust counter electrodes by magnetron sputtering technique for dye-sensitized solar cells.